Filipino female juvenile deliquents an exploratory study of their level of intelligence, personality, and attitudes towards the self and selected social figures.[article]. - Carlota, Annadaisy J.
The article describes the intellectual and personality characteristics of Filipino female juvenile deliquents as well as their attitudes towards the self and selected social figures. The participants of the study included 31 deliquents who were matched with an equal number of non-deliquent controls on variables of age, sex and socio-economic status. All participants were administered the Raven's Standard Progress Matrices (RSPM), the High School Personality Questionnaire (RSPQ), the Rohde Sentence Completion Test(RSCT) and selected cards from the Thematic Apperception Test(TAT). The results showed that deliquents obtained significantly lower intellegence scores on two indicators, namely, the RSPM and the intelligence factor of the HSPQ. Testing with the HSPQ also revealed that deliquents, compared to non-deliquents, are: less moralistic, more inclined to disregard rules, and more impenitent; critical of people, cool and their interpersonal interaction; inclined to disregard their social obligations; more emotionally undemonstrative. Finally, analysis of the data from the RSCT and TAT indicate that more deliquents display a strong abasive attitude towards the self. They are also more critical of their abilities and their behaviors. Fewer deliquents have a positive attitude towards the members of their families and towards peers, of the same and the opposite sex. An attempt to explain the findings from a social-learning point of view was taken.